Aktivitas Media Monitoring pada Media Online oleh PT Phapros Tbk - Amalia, Riztria Zahra; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the activities of media monitoring on online media by PR of PT Phapros Tbk, using the concept of Media Monitoring Stages by Isywandi Syahputra. The research question based on this concept is how the data mining stage, data processing stage, and analysis and reporting stage in monitoring media activities on online media by PT Phapros Tbk. This research uses constructivism paradigm and qualitative approach, with qualitative descriptive method. Data were obtained through data collection techniques, namely in-depth interviews, observation, and documentation studies. The research results are media monitoring activities by PR of PT Phapros Tbk are carried out: Data Mining stage consists of determining keywords, collaborating with media consultants, and searching for data on online media; Data Processing stage consists of data categorization, and determining news tonality; and Analysis and Reporting Stage consists of analysis of data results, data reporting, and utilization of data results.